Challenges in the development of digital competence in secondary school teachers - Ely Ruiz del Hoyo Loeza; Sergio Humberto Quiñonez Pech; Alfredo Zapata González (Universidad de Guadalajara, 2023)
Currently, due to emerging paradigms of teaching and learning as a result of health contingency, digital competence has become a necessity in educational centers. Furthemore, the new teaching role is no longer just that of being a facilitator of face-to-face learning, but now it generates knowledge, communicates and transmits emotions through various virtual environments. This paper has as aim to identify the level of digital competence in secondary level teachers, as well as the factors associated with it. The study has a quantitative approach, with a correlational scope, transactional temporality, with an observational prediction control and a retrospective chronological order of events. As a result of the research, a low level of digital competence was identified among secondary school teachers in Merida, Yucatan, Mexico. There was evidence that the factors that were significantly associated with this competence were age and training in the use of Information and Communication Technologies (ICT). This sets the foundations for the design of teacher training proposals focused on the development of their digital competence.